(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
The preliminary results of the 1984 Italian Geological Expedition to Zanskar are given as a general account of the stratigraphy of the Tethys Himalaya succession. The sedimentary sequence has been subdivided in three parts, from Late Precambrian to Eocene.